Reformasi Mutu Pendidikan Melalui Peningkatan Profesionalisme Guru - Ahmad Hariyadi (LPPM Press, 2015)
The vision of national education development is “Realization of intelligent, productive,and noble people in Indonesia.” Section 8 states that “Teachers have to be obligatoryto have academic qualification, competence, educator certificate, be physically andmentally health, and have the ability to realize the goal of national education”. NationalEducation Standard is an aim as one of the quality education assurance to be properlyimplemented and not be just a symbol. National Education Standard, whcih includescontent and process standard, graduate competency, educator and educational personnel,facility and infrastructure, management, financing, educational assessment, accreditationand others, are major requirement for the government that needs standard competencyand quality of education. Teacher is a human component for the learning process that hasa role of reaching the determined educational goals. Therefore, teaching is a professionalwork, because of the technique and procedure use which stand on an intellectual basis onbehalf of the other benefits.